2017
DOI: 10.3892/mmr.2017.8144
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of 14-3-3β inhibits proliferation and migration in osteosarcoma cells

Abstract: The 14-3-3 protein isoform β (14‑3‑3β), which is an intracellular adaptor protein that exists in all eukaryotic organisms, is highly expressed in many cancer tissues, including glioma, lung carcinoma and breast cancer. However, 14‑3‑3β expression and function in osteosarcoma progression remain unknown. In the present study, the endogenous expression of 14‑3‑3β was assessed in osteosarcoma samples and the effect of 14‑3‑3β knockdown was examined in human osteosarcoma MG63 cells using small interfering RNA (siRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…After 14-3-3 β siRNA application, survival rate of the transplanted mice was enhanced, and tumor volume and weight were decreased, which indicated that the effect of hypoxia on tumor growth was reversed by 14-3-3 β knockdown. In addition, a previous study also reported that 14-3-3 β downregulation inhibits osteosarcoma cell proliferation and migration [ 53 ]. The present study therefore hypothesized that 14-3-3 β may serve a crucial role in the hypoxia-induced tumor growth in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…After 14-3-3 β siRNA application, survival rate of the transplanted mice was enhanced, and tumor volume and weight were decreased, which indicated that the effect of hypoxia on tumor growth was reversed by 14-3-3 β knockdown. In addition, a previous study also reported that 14-3-3 β downregulation inhibits osteosarcoma cell proliferation and migration [ 53 ]. The present study therefore hypothesized that 14-3-3 β may serve a crucial role in the hypoxia-induced tumor growth in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…[88] Osteosarcoma 14-3-3β isoform demonstrated significant upregulation in osteosarcoma samples. [89] Colorectal cancer (CRC) Elevated 14-3-3ζ expression in CRC (79.5%) compared with control tissues (21.9%) in immunohistochemistry (IHC).…”
Section: Lung Cancermentioning
confidence: 99%
“…Therefore, the overexpression of 14-3-3 proteins (except 14-3-3σ) in many cancers may be a target for therapeutic applications. For instance, the 14-3-3β siRNA knockdown has been reported to decrease the levels of cyclin D1 significantly, v-myc avian myelocytomatosis viral oncogene homologue and matrix metallopeptidase 9 (MMP-9) in osteosarcoma MG63 cancer cells [89].…”
Section: Potential Therapeutic Application and Futurementioning
confidence: 99%
“…Mitochondrial biogenesis is necessary during muscle regeneration ( Wu et al, 2018 ; Niu et al, 2021 ). Under the pressure of differentiation, myoblasts require more energy to maintain cell remodeling; accordingly mitochondria are constantly splitting in cells, and mitochondrial autophagy is markedly increased ( Hardy et al, 2016 ; Bloemberg and Quadrilatero, 2019 ).…”
Section: The Role Of Mitochondria In Myogenesis Regeneration and Musc...mentioning
confidence: 99%